Retrospective study to identify trigeminal–cervical ocular referred pain as a new causative entity of ocular pain - Tseng SC; Cheng AM; Fu Y (Journal of Pain Research, 2017)
Scheffer CG Tseng,1 Anny MS Cheng,1,2 Yao Fu3 1Ocular Surface Center, 2Florida International University, Herbert Wertheim College of Medicine, Miami, FL, USA; 3Department of Ophthalmology, Ninth People’s Hospital, Medical School of Shanghai Jiaotong University, Shanghai, People’s Republic of China Purpose: To determine the prevalence and clinical characteristics of trigeminal–cervical (TC) ocular referred pain.Methods: A retrospective study of 1,680 patients seen during 2002–2010 was performed in an ocular surface specialty center to identify patients with or without TC pain defined as ocular pain with ipsilateral trigger points located at the occipital region. Patients with refractory TC pain despite topical anesthetics and conventional treatments received interventional injection to each trigger point.Results: A total of 81 (4.8%) patients (study group) with TC pain and 241 patients (control group) without TC pain were identified out of the 1,680 patients over an 8 year period. There was no difference in age, gender, prior surgeries, medications, non-pain symptoms, pain laterality, and concomitant ocular diseases between the 2 groups. Multivariate regression analysis showed that patients with TC pain had a significant correlation with persistent deep ocular pain, ipsilateral trigger points (f2=99, p<0.001) but not headaches (f2=0.09, p=0.5). Injection at the trigger points achieved complete or partial pain resolution with a low recurrence rate in 43 of 45 (96%) patients with TC pain.Conclusion: TC pain defined herein may be a different entity of ocular pain and can indeed be differentiated from other ocular pain by the referral character so that one may avoid mislabeling it as undetermined or as a reason to unnecessarily overtreat concomitant ocular diseases. Keywords: headache, new ocular pain, referred pain, trigeminal–cervical, trigger point, occipital neuralgia